2015
DOI: 10.1038/nrm3953
|View full text |Cite
|
Sign up to set email alerts
|

Getting up to speed with transcription elongation by RNA polymerase II

Abstract: Recent advances in sequencing techniques that measure nascent transcripts and that reveal the positioning of RNA polymerase II (Pol II) have shown that the pausing of Pol II in promoter-proximal regions and its release to initiate a phase of productive elongation are key steps in transcription regulation. Moreover, after the release of Pol II from the promoter-proximal region, elongation rates are highly dynamic throughout the transcription of a gene, and vary on a gene-by-gene basis. Interestingly, Pol II elo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
811
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 734 publications
(861 citation statements)
references
References 135 publications
25
811
2
5
Order By: Relevance
“…The catalytic cycle of RNAP can be interrupted by pauses of various natures that play important roles in genetic regulation in all organisms, from the classic systems of transcription attenuation and their variations in bacteria (1) to recently discovered widespread promoter-proximal pausing in eukaryotes (2). The pausing serves to activate or repress transcription rapidly at specific genomic sites in response to regulatory stimuli and to coordinate RNA synthesis with other genetic processes (e.g., DNA replication and repair, RNA translation in bacteria) (1,(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…The catalytic cycle of RNAP can be interrupted by pauses of various natures that play important roles in genetic regulation in all organisms, from the classic systems of transcription attenuation and their variations in bacteria (1) to recently discovered widespread promoter-proximal pausing in eukaryotes (2). The pausing serves to activate or repress transcription rapidly at specific genomic sites in response to regulatory stimuli and to coordinate RNA synthesis with other genetic processes (e.g., DNA replication and repair, RNA translation in bacteria) (1,(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…[15][16][17][29][30][31] Mammalian NET-seq demonstrated RNAPII S5P enrichment at 5 0 and 3 0 splice sites 15 and phospho-specific RNAPII immunoprecipitations have revealed that RNAPII S5P interacts with key proteins involved spliceosomal assembly. 15,16,29 For a detailed reviews on co-transcriptional splicing, we refer the reader to Saldi et al (2016) and Jonkers et al (2015) 25,32 . Spliceosome assembly is a multi-step process that occurs on the pre-mRNA transcript, starting with recruitment of U1 snRNP at the 5 0 splice site 33 and U2 snRNP to the exonic nucleosome at the 3SS 34 and then at the branch point to form the pre-spliceosome (complex A).…”
Section: Splicing Checkpointmentioning
confidence: 99%
“…22 Interestingly, the mean exon length in mouse and humans is 147 nt and corresponds to the length of DNA wrapped around a nucleosome. 23 For a detailed reviews on RNAPII pausing, we refer the reader to Liu et al (2015) and Jonkers et al (2015) 24,25 . RNAPII S5P/S7P and RNAPII that is hypo-phosphorylated at S2, highly correlate genome wide with H3K4me3 and PHF13 enrichment, at or just downstream of the TSSs.…”
Section: Promoter/promoter Proximal Pausingmentioning
confidence: 99%
“…(1)]; and high-resolution genomic approaches and imaging techniques provided the kinetics of the polymerase movement and the dynamics of cotranscriptional processes, such as splicing and chromatin remodelling [reviewed in Refs. (2,3)]. …”
Section: Introductionmentioning
confidence: 99%